Trichophyton Tonsurans Induced Recurrent Onychomadesis in a Very Young Infant. Issue 3 (3rd February 2012) - Khanna, Deepshikha; Goel, Alka; Kedar, Ashwini; Manchanda, Vikas; Agarwal, Swastika
<x xml:space="preserve">Abstract</x> Abstract: Onychomadesis, or nail shedding, is rarely seen in children and can be due to stress, systemic illnesses, trauma, and drug therapy or may be idiopathic. Fungal infection of the nail is only rarely reported as a cause of onychomadesis. We present here a case of Trichophyton tonsurans–induced onychomycosis and resultant onychomadesis in a 9‐month‐old boy with onset of lesions at 2 weeks of life.